DEVELOPMENT OF OASE KASIH-BASED PANCASILA EDUCATION TEACHING MATERIALS TO FOSTER BROTHERHOOD AND SOCIAL SOLIDARITY AMONG ELEMENTARY SCHOOL STUDENTS - Paskaria Simbolon; Yakobus Ndona; Surya Dharma; Daulat Saragi; Samsidar Tanjung; Yusnadi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aimed to develop, validate, and evaluate the effectiveness of OASE KASIH-based Pancasila Education teaching materials in fostering brotherhood and social solidarity among elementary school students. The study was motivated by the limited availability of character-oriented teaching materials that systematically integrate values of brotherhood, empathy, cooperation, and social responsibility into Pancasila Education learning. A Research and Development (R&D) approach employing the ADDIE model was adopted, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at St. Francis of Assisi Elementary School, Binjai, involving Grade V students. Data were collected through expert validation sheets, observation guides, interviews, student response questionnaires, and learning achievement tests. The developed teaching materials integrated the OASE KASIH approach, which emphasizes observation, sensitivity, authentic understanding, affection, attitude selection, action, and spiritual reflection. The validation results demonstrated a high level of feasibility, with scores of 91.6% from content experts, 91.1% from media experts, and 93.5% from language experts. Practicality testing showed positive responses, achieving 89.95% in individual trials and 86.81% in small-group trials. The effectiveness test revealed a significant improvement in students’ social character, with the mean pretest score increasing from 58.47 to a posttest score of 89.12. The average N-Gain score was 0.7423, indicating a high level of improvement, while the paired-samples t-test yielded a significance value of 0.000 (p < 0.05), confirming statistically significant differences between pretest and posttest scores. These findings indicate that the OASE KASIH-based teaching materials are valid, practical, and effective in strengthening students’ brotherhood and social solidarity. The study contributes an innovative character-based instructional resource for enhancing value-oriented Pancasila Education in elementary schools.